'Ajami as wood paneling craft in Syrian art and interior ornament - Baydoun, Ziad; Kamaruddin, Zumahiran (2015)
The Arabic term ‘Ajami means Persian or Non-Arabic is used to describe the technique and the ornaments as well as the interior as a whole. The ‘Ajami decorations became very prominent throughout the Ottoman Empire after the decline of tile production and rose to sophisticated levels of art in Syria. ‘Ajami decoration is almost universal in the interior adornment of Syrian houses and palaces, especially during the seventeenth to late eighteenth century. However, nowadays, it can be seen that this beautiful decorative painting technique is now-forgotten by modern generation and would gradually become one of an extinct art in Syria. This deep-rooted art has a rich history in the country, however, the production and technique of ‘Ajami has not been fully embraced and recorded in past studies. Secondary data was obtained from review of related literatures and researches that were published in the past few decades. This paper presents Damascus and Aleppo ‘Ajami rooms as case studies. The methods of historical and visual analysis were adopted to investigate the art and craft of ‘Ajami in the two rooms. The results of the analysis are presented simultaneously with the information that characterizes the valuable and historical art of ‘Ajami as wood panelling for art and interior adornment. Findings of the research suggest for further investigation on the lost techniques and the original surface appearance of the ‘Ajami, which are essential in order to sustain its historical aesthetic value and its antecedents among traditional artisans.